Whole blood assessment of antigen specific cellular immune response by real time quantitative PCR: a versatile monitoring and discovery tool - Schultz-Thater, Elke (BioMed Central, 2008)
BACKGROUND: Monitoring of cellular immune responses is indispensable in a number of clinical research areas, including microbiology, virology, oncology and autoimmunity. Purification and culture of peripheral blood mononuclear cells and rapid access to specialized equipment are usually required. We developed a whole blood (WB) technique monitoring antigen specific cellular immune response in vaccinated or naturally sensitized individuals. METHODS: WB (300 μl) was incubated at 37°C with specific antigens, in the form of peptides or commercial vaccines for 5–16 hours. Following RNAlater addition to stabilize RNA, the mixture could be stored over one week at room temperature or at 4°C. Total RNA was then extracted, reverse transcribed and amplified in quantitative real-time PCR (qRT-PCR) assays with primers and probes specific for cytokine and/or chemokine genes. RESULTS: Spiking experiments demonstrated that this technique could detect antigen specific cytokine gene expression from 50 cytotoxic T lymphocytes (CTL) diluted in 300 μl WB. Furthermore, the high sensitivity of this method could be confirmed ex-vivo by the successful detection of CD8+ T cell responses against HCMV, EBV and influenza virus derived HLA-A0201 restricted epitopes, which was significantly correlated with specific multimer staining. Importantly, a highly significant (p = 0.000009) correlation between hepatitis B surface antigen (HBsAg) stimulated IL-2 gene expression, as detectable in WB, and specific antibody titers was observed in donors vaccinated against hepatitis B virus (HBV) between six months and twenty years before the tests. To identify additional markers of potential clinical relevance, expression of chemokine genes was also evaluated. Indeed, HBsAg stimulated expression of MIP-1β (CCL4) gene was highly significantly (p = 0.0006) correlated with specific antibody titers. Moreover, a longitudinal study on response to influenza vaccine demonstrated a significant increase of antigen specific IFN-γ gene expression two weeks after immunization, declining thereafter, whereas increased IL-2 gene expression was still detectable four months after vaccination. CONCLUSION: This method, easily amenable to automation, might qualify as technology of choice for high throughput screening of immune responses to large panels of antigens from cohorts of donors. Although analysis of cytokine gene expression requires adequate laboratory infrastructure, initial antigen stimulation and storage of test probes can be performed with minimal equipment and time requirements. This might prove important in "field" studies with difficult access to laboratory facilities.